In Silico Docking Analysis Of Curcumin - An Inhibitor For Obesity - P. ARCHANA; N. SATHISHKUMAR; N. BHARATHI (International Journal of Pharma and Bio Sciences, 2010)
Obesity refers to abnormal or excessive fat accumulation in the human body which results in health risk. Obesity leads to several risk factors for a number of chronic diseases such as diabetes, cardiovascular diseases, cancer and osteoarthritis. Curcumin, the major polyphenol of turmeric spice, is a member of the ginger family (Zingiberaceae). Growth of adipose tissue is enhanced by the process of angiogenesis. Curcumin, by its antiangiogenic activity may suppress the growth of adipose tissue. This study attempts to curtail the action of fat mass and obesity protein (FTO) by docking with Curcumin. Curcumin acts as an inhibitor and suppresses the action of obesity protein and hence may contribute to lower body fat and body weight gain. Some of the commonly used drugs to treat obesity includes Orlistat, Sibutramine and Rimonabant. These drugs were subjected to docking analysis for comparative studies.